Satellite Navigation Systems – An Avoided Target? - Luparu, Dorian (Romanian military thinking : military theory and science journal, 2022)
In the current geopolitical context, the Black Sea region has become the scene of the conflict in which a wide range of weapons and ammunition are used. It is their directing/guiding by using signals transmitted by satellite navigation networks – GNSS that categorically makes the difference. Their contribution can be instantly noticed, even though it is not a novelty. The weapons that benefited from the augmentation of the satellite signal proved the accuracy of their shots. This is the reason why the actions of jamming or falsification of the satellite signal appeared in the battlefield and even threats of GNSS attack were launched. In the present article, I intend disambiguation of the subject, in an attempt to delimit military declarations from political ones, in the space environment, which has become essential in the conduct of modern military actions.